Requirements for a Product Lifecycle Management System Using Internet of Things and Big Data Analytics for Product-as-a-Service - Sakao, Tomohiko; Nordholm, Alex Kim (Frontiers in Sustainability, 2021)
Product-as-a-service (PaaS) offerings have advantages and potential for transforming societies to a circular economy and for improving environmental performance. Original equipment manufacturers providing PaaS offerings take higher responsibility for product performances in the use phase than those selling products. This responsibility can be supported by digital technologies such as the Internet of Things (IoT) and big data analytics (BDA). However, insights on how data of product designs and in-use services are managed for PaaS offerings in product lifecycle management (PLM) software are scarce. This mini-review first gives an account of extant major research works that successfully applied BDA, a specific technique of artificial intelligence (AI), to cases in industry through a systematic literature review. Then, these works are analysed to capture requirements for a PLM system that will exploit the IoT and BDA for PaaS offerings. The captured requirements are summarized as 1) facilitate product and service integration, 2) address multiple lifecycles, 3) adopt an ontology approach encompassing several product standards, and 4) include reading data to process in an interoperation layer.